Utilização do fruto de moringa oleifera lam no processo de biossorção de chumbo (ii) de águas contaminadas - Tavares, Fernanda de Oliveira (2016)
Lead is a heavy metals considered highly toxic, responsible for causing a number of health problems as well as being extremely harmful to flora and fauna. Given this fact, several techniques have been studied for removal this metal from contaminated water, among which stands out the adsorption process. In this sense, the objective of this study was to evaluate the potential of lead (II) removal from contaminated water using hulls of seeds, seeds and pods of Moringa oleifera Lam (moringa) as biosorbents, in its natural form, and after application of chemical treatment (acidic and basic), thus totaling 9 biosorbents. First the characterization studies of the parts of fruits of Moringa were conducted to evaluate the effect promoted by the applied chemical treatment and also to provide a better understanding of action mechanism involved in biosorption processes of lead ions. The characterization analyzes showed that the jug can be a potential biosorbent and the application of basic chemical treatment may promote changes in the structure of the material which promote the biosorption of the metal analyzed. After the step of characterization the biosorption process was studied from artificially water contaminated by lead. In biosorption study evaluated the influence of some parameters such as contact time, pH, temperature, biosorbent dose and stirring speed in the adsorption. Kinetic modeling of the data was analyzed as to the models of pseudo first order and pseudo second order, and the isotherms as the best fit by adsorption models of Langmuir and Freundlich. Thermodynamic studies were used to better understand the biosorption process. From the studied parameters, it was possible to obtain optimum conditions for all analyzed biosorbents, 30 minutes required for the occurrence of equilibrium, pH range between 5-6, 25 ° C, 0.5 grams of biosorvent dosage and 100 rpm for agitation speed. The kinetic model of pseudo-second order was the best fit to the experimental data. The isotherm model that showed the best fit to the experimental data for the hulls of seeds and seed, was the model proposed by Freundlich and for pods, the Langmuir model. The analysis of the thermodynamic data obtained showed that the adsorption process is favorable and of exothermic nature. Through the results has been possible to conclude that the parties assessed of moringa are efficient in biosorption of lead (II) from contamined water.